(untitled) (Ciudades, 2018)
Since a few years ago, possibly decades, the urban practice flows orphaned, its supports increasingly circumstantial and imprecise, the reference theories are questioned from nearly all points of view and its goals change moved by interests sometimes unutterable; however, there are moments in which the urban sintomatology seems to verify the theory of eternal return, moments in which history looks to the past to restart in a different way, as if there existed an explecit will to acept the world as it is, closed in itself, with a purely immanent signification.